Effects of Aging on Hemodynamic Kinetics in Different Intensities of Dynamic Exercise - Borghi-Ricardo, Matheus; Simões, Rodrigo Polaquini; Santos, Daniel Augusto; Archiza, Bruno; Borghi-Silva, Audrey (International Journal of Sports Medicine, 2021)
Healthy aging hemodynamics is known to exhibit a time-dependent loss of function. We aimed at verifying whether older men would have a slowed cardiac output and stroke volume dynamics in response to the onset (“on”) and on recovery (“off”) of exercise in comparison to young men. Twenty healthy active men (10 young and 10 older) were recruited. Participants performed an incremental cardiopulmonary exercise testing on a cycle ergometer, and on another day, 3 constant workload tests in different intensities. Compared to younger, older men exhibited a slower cardiac output and stroke volume dynamics in both on and off transients for all exercise intensities (all P < 0.05). During higher intensities, both younger and older men had slower hemodynamic kinetics compared to lower intensities (all P < 0.05). There was strong negative relationship between the time constant of cardiac output on-kinetics during high-intensity with maximal exercise performance in both groups (r = –0.88, P < 0.01). We interpret these findings to mean that healthy older men have slowed hemodynamic kinetics compared to younger, but this difference becomes less evident in higher intensities of exercise.
Keywords: cardiovascular health; older adults; central hemodynamic; aging